Case report: A case of pseudo-acute kidney injury due to cyclin-dependent kinase inhibitor - Errabelli, Praveen; Lathiya, Maulik; Singh, Devender (Frontiers in Nephrology, 2024)
Various classes of targeted therapies have emerged in the last few years, which have revolutionized cancer treatment, and improved the prognosis and survival of cancer patients. Unfortunately, these agents have serious toxic effects on the kidneys. Some of the toxic effects are hypertension, acute kidney injury (AKI), and proteinuria. One interesting phenomenon that has emerged recently is pseudo-acute kidney injury due to the interference with the tubular secretion of creatinine by some of the targeted therapeutic agents. Understanding this physiology is needed to avoid unnecessary investigation and withholding of lifesaving chemo regimen. Alternative methods to assess renal function such as cystatin C-based estimated glomerular filtration rate (eGFR) can differentiate true AKI from pseudo-AKI. Here, we describe one such case of pseudo-AKI from cyclin-dependent kinase (CDK) 4/6 inhibitor, abemaciclib, which inhibits tubular secretion of creatinine. Using cystatin-C-based eGFR revealed pseudo-AKI in this case.